Conductive polyaniline-mediated efficient electron transfer in Z-scheme photocatalysts for enhanced overall water splitting. Issue 5 (21st December 2020) - Zhang, Zhengguo; Xie, Guangrong; Wang, Fang; Min, Shixiong
Abstract : Conductive polyaniline as a solid electron mediator efficiently shuttles photoexcited electrons from BiVO4 to Ru/SrTiO3 :Rh for efficient overall water splitting under visible light irradiation ( λ ≥ 420 nm). Abstract : Here, we demonstrate that conductive polyaniline (PANI) can function as a solid redox mediator to efficiently shuttle photogenerated electrons from BiVO4 to Ru/SrTiO3 :Rh, thus greatly promoting the separation of electrons and holes and nearly quadrupling the overall water splitting activity under visible light irradiation ( λ ≥ 420 nm).